ANALISIS PENERIMAAN SPREADSHEET METHOD UNTUK PENYUSUNAN LAPORAN KEUANGAN OLEH MAHASISWA (Studi kasus pada Mahasiswa Akuntansi FEB Unika Atma Jaya Jakarta) - Weli .; Jessica Widjaja (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
The Introduction to Accounting is main course that must be taken by the economics students. However, the content of the subject was delivered manually, on the other hand in the information technology era the teaching methods for subject can be performed using computerized system for example by using a spreadsheet method. By using the formula, worksheets can be connected each other. The aim of this study is to analyze the level of student acceptance in using spreadsheet method. This is experimental research method on 83 economics students and accompanied by online questionnaires before and after training. Question item questionnaire was prepared based on Technology Acceptance Model. The results of the paired t-test indicate that student perception is changing as well as there is a positive student acceptance in using spreadsheet for prepare accounting statement